Scientific production of the professors of physical education and sport in Catalonia (2005-2009 versus 2010-2014) - Hernández González, V.; Reverter-Masia, J.; Jové-Deltell, C. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
This work is a descriptive, comparative and correlational study of document analysis. The goal is to understand the evolution of scientific production of the professors of Physical Education and Sports (EF&D) Catalans during the 2010-2014 five-year period and compare it with the previous five years, analyzing it through journal articles in the database WoS. The sample involved 423 teachers. During the five years 2010-2014, were published 344 documents (68.8 ± 24 documents by year), 170% more than in 2005-2009 (127 documents, 25.4 ± 33 documents). During the five years 2010-2014, a significant increase was observed in the total production of documents (p<0.05), with an average annual growth of 34%. The correlations between the numbers of citations index h is positive in both five-year periods (0.93 and 0.89). The scientific production of (EF&D) teachers increased apace in quantity during the 2010-2014, but the IF of the journals in which they published descended.